Representaciones sociales de cinco mujeres del área administrativa de la UAN acerca del conflicto entre el rol laboral y familiar (2017)
The present research had as the objective to analyzing the social representations of five women from the administrative area of the Antonio Nariño University about the conflict between the work and family role. The type of research was qualitative, developed within a historicalhermeneutic design, with the proposite to interpret and understand, through the life history of the participants this conflict. Therefore, data analysis allows to describe the opinions, beliefs and information of each of them, finding as a result that there is a work-family conflict, because there is a dissonance in the fulfillment of roles, generating an overload and interference in the execution of their duties and biopsychosocial effects.